The effects of forest types and age groups on forest provisioning and supporting service value in Sanhu Nature Reserve, Northeast China - Liu, Qiang; Cheng, Yan; Yu, Fang; Fan, Chunnan (Frontiers in Forests and Global Change, 2023)
The promotion of forest resource protection and sustainable development relies greatly on the value of forest ecosystem services. In Jilin Songhuajiang Sanhu National Nature Reserve in Northeast China, a total of 169 sample plots were examined and analyzed to evaluate the provisioning and supporting services provided by the forest ecosystem. The study revealed that the near-mature and over-mature Fraxinus mandshurica forest have relatively high timber supply and species resources conservation values per unit area, respectively. Furthermore, the mature Betula platyphylla forest has the highest forest nutrient retention value, while the near-mature Juglans mandshurica forest has the highest soil conservation value, with the nitrogen fixation value accounting for the highest proportion. The forest ecosystem services in the reserve have a total value of 659.07 million $⋅y–1. The main contributors to the value are the services of soil fertilizer conservation, timber supply, and species resources conservation, with the mixed broad-leaved forest and Quercus mongolica forest being the main contributors, accounting for 63.1 and 18.8% of the total value, respectively. Nonetheless, the service value of per unit area in J. mandshurica forest is the highest. Near-mature and mature forests are the main contributors to the total value, accounting for 42.3 and 34.9%, respectively. Forest lands exhibit significant variations in the values of provisioning and supporting services across different stand types and age groups.